Practice and experience of shift rotation in the general ward, CCU and catheterization unit of cardiology (心内科普通病房、CCU、导管室轮转实施及体会) - ZHOU Xiaoyan (周晓艳); SHEN Juan (沈娟); WANG Zhaojia (王兆嘉); SUN Tingting (孙婷婷); ZHANG Yue (张悦); WANG Xingyu (王星予); CUI Liu (崔柳); TANG Shuo (唐硕) (Journal of International Translational Medicine Limited, 2021)
This paper summarized the practice and experience of shift rotation in the general ward, CCU and catheterization unit of cardiology. The practice of shift rotation included rotation background of rotation, setting up of a team of clinical teachers, establishing the teaching program, training before shift rotation and related assessment. Nurses were trained in professional skills, and implementation of shift rotation had relieved pressure on nursing human resources. (本文主要对心内科普通病房、CCU和导管室3个护理单元实施轮转的相关经验进行总结, 主要包括轮转的背景、带教老师的确定、教学内容的制定、轮转前的培训以及相关考核等, 通过实施轮转, 护士的业务能力明显提高, 缓解了科室人力资源紧张的情况。)